Ain't no man: Female masculinity in Android game Legend of the PHOENIX - Adelia, Silvy; Dirgantari, Alfi; Hirano, Shun; Wedawati, Mamik; Ridha, Firly; Koiri, Much (LITERA, 2024)
This study performs content analysis on an Android game titled Legend of the Phoenix. Legend of the Phoenix, commonly known as LoP, is an otome (girl) game released by Modo Game in 2020. Like most otome games, Legend of the Phoenix revolves around the journey of a young woman who is given a second chance at life after her first ends tragically. The player takes the role of this young woman and has to complete various missions and storylines in order to complete the game. This study aims to find messages about gender presented in the game by analyzing its visual and narrative content. It focuses on identifying female masculinity in the special recruitment group of Female General or Heroine. The game characters being analyzed are the four Generals in Legend of the Phoenix"”Hua Mulan, Mu Guiying, Liang Hongyu, and Qin Liangyu. They are examined in terms of role, abilities, and appearance and their relation to the concept of female masculinity introduced by Halberstam. The result shows that the Female General belongs to Femme Pretender type. It means that the characters of Hua Mulan, Mu Guiying, Liang Hongyu, and Qin Liangyu possess masculine traits (role and abilities) while also keeping their female appearance (physical and outfit).